Hydrogeology of the Mackenzie Basin - Cooksey, Kirsty (University of Canterbury. Geological Sciences, 2008)
The intermontane Mackenzie Basin is located within the central South Island of New Zealand. The glacial basin contains three glacial lakes which are used for hydroelectric power generation via a canal system that links the lakes. The basin is an area of climate extremes, low rainfall, high summer temperatures, and snowy winters. The area is predominantly used for pastoral farming, however farming practices are changing and, combined with an increasing population, there is a need to define the groundwater resources to enable sustainable resource management. Little is currently known about the hydrogeological system within the Mackenzie Basin, and what is known is from investigations carried out during the construction of the canal system from 1935 to 1985. There are four glacial formations that overlie Tertiary sequences and Torlesse bedrock. However, due to the glacial processes that have been ongoing over at least the last 300 ka, determining the occurrence and extent of groundwater within the outwash gravels is difficult. It is suggested that the permeability of the formations decreases with depth, therefore horizontal and vertical hydraulic conductivity decrease with depth. A shallow groundwater table is present within the Post Glacial Alluvial Gravels which is recharged directly from fast flowing streams and rivers as well as rainfall. It appears that this shallow system moves rapidly through the system and it is unlikely that the water infiltrates downwards to recharge the deeper groundwater system. It is thought that a deep groundwater system flows preferentially through the Mt John Outwash Gravels, being the second youngest glacial formation. Water chemistry and age dating tracer analysis indicate that the deeper groundwater is over 80 years old and that the groundwater system is recharging slowly. The shallow groundwater in the Post Glacial Alluvial Gravels and within the major fans to the east of the basin is 10 to 20 years in age. Baseline data such as water chemistry, groundwater levels, and surface ...